Transcriptional regulation of the phosphoenolpyruvate carboxykinase gene by cooperation between hepatic nuclear factors. - Yanuka-Kashles, O (Mol Cell Biol, 1994)
To study the transcriptional regulation of the liver gluconeogenic phenotype, the underdifferentiated mouse Hepa-1c1c7 (Hepa) hepatoma cell line was used. These cells mimicked the fetal liver by appreciably expressing the alpha-fetoprotein and albumin genes but not the phosphoenolpyruvate carboxykinase (PEPCK) gene. Unlike the fetal liver, however, Hepa cells failed to express the early-expressed factors hepatocyte nuclear factor 1 alpha (HNF-1 alpha) and HNF-4 and the late-expressed factor C/EBP alpha, thereby providing a suitable system for examining possible cooperation between these factors in the transcriptional regulation of the PEPCK gene. Transient transfection assays of a chimeric PEPCK-chloramphenicol acetyltransferase construct showed a residual PEPCK promoter activity in the Hepa cell line, which was slightly stimulated by cotransfection with a single transcription factor from either the C/EBP family or HNF-1 alpha but not at all affected by cotransfection of HNF-4. In contrast, cotransfection of the PEPCK construct with members from the C/EBP family plus HNF-1 alpha resulted in a synergistic stimulation of the PEPCK promoter activity. This synergistic effect depended on the presence in the PEPCK promoter region of the HNF-1 recognition sequence and on the presence of two C/EBP recognition sequences. The results demonstrate a requirement for coexistence and cooperation between early and late liver-enriched transcription factors in the transcriptional regulation of the PEPCK gene. In addition, the results suggest redundancy between members of the C/EBP family of transcription factors in the regulation of PEPCK gene expression. IMAGES: